TINJAUAN HUKUM ISLAM TENTANG PENETAPAN UANG PANNAI’ (NAIK) DAN PENETAPAN MAHAR DALAM PERNIKAHAN MASYARAKAT LEMBAH SUBUR. (Studi Kasus Desa Lembah Subur Kec. Dangia Kab. Kolaka Timur Prov. Sulawesi Tenggara) - Askar Saputra (Jurnal Syariah Hukum Islam, 2019)
The main problem of this research is to study, analyze and review in Islamic law the determination of increased money and the determination of the dowry that occurs in the marriage process of the people of Lembah Subur Village. Which is relatively high in the stipulation, this is because this determination does not see the ability of the prospective groom but sees the level of family popularity, education and economic status of the prospective bride. The determination made by the community in Lembah Subur Village is the biggest phenomenon or fear for men who have the desire to convey their good intentions to women who have these criteria. In this matter, this research directly examines the process of determining pannai 'money and dowry in the Islamic law review. The research method used includes qualitative research; the objects of research carried out include the local government, religious leaders and the people of Lembah Subur; The research method used is the method of interviewing the object of the researcher; The techniques used in this study use inductive data analysis, so the researcher will describe what he sees, hears, sees and asks. Based on the results of the research, it turns out that the Bugis community, especially in Lembah Subur Village, considers that giving Dui 'menre is a tradition given by men to women whose function is used as costs to carry out the wedding party from the beginning of preparation and until the wedding ceremony is over. The aim is to give respect to the family of the woman. The position of Dui 'menre in bugis customary marriage is one of the prerequisites, because if there is no Dui' menre there is no marriage. Islam does not regulate the provisions of Dui 'menre, but the law is permissible. Islam does not prohibit the giving of Dui 'menre in a marriage that is in the Bugis custom because there is no argument that explains it. The important thing is that giving Dui 'menre does not contradict syri'at and the determination of the value of Dui' menre does not have an element of compulsion, according to the abilities and abilities of men. However, in this study the authors get the impact of high panai money (Naik). As for the impact of the high determination of the number of Dui 'menre, namely canceling marriage, the relationship between the two families can become tenuous, many men are reluctant to marry, many spinster, cross .